Criticism of Interpretations of Women's Obligation to Cover The Aurat - Herliani (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2024)
If there are currently various models of Muslim fashion, it is different from the conditions of 1987-1989. At that time, in some places, covering the aurat with a neat hood received discriminatory treatment and was considered strange, even suspected. Perhaps ignorance of society and lack of example from teachers are among the contributing factors. There was an opinion that veiling was not mandatory until the Indonesian mufasir, Quraish Shihab, became the target of discussion. Even today there are still those who keep their distance from the book of tafsir. For academics, it is necessary to correct misunderstandings so that there are no unhealthy expectations and the public is not confused. The purpose of this study was to obtain a comprehensive answer regarding the limits of women's aurat according to the four mufasir and the law of closing the aurat. The method is in the form of criticism by comparing. The book of tafsir that is the object of research is the book of tafsir by al-Qurṭubi, as-Sa'di, Hamka, and Quraish Shihab related to surah an-Nur verse 31. The result is that all four commentaries agree that covering the aurat is mandatory, although al-Miṣbāh it is unnatural to state against those who do not wear veils or who show part of their hands that they "have definitively violated religious instructions". The reason is that the Qur'an does not mention the limits of the aurat and even scholars when discussing it differ in opinion. The difference is only in the aurat limit. Some say a woman's entire body is aurat, some leave her face and palms. For followers of the Hanafi school as mentioned in al-Miṣbāḥ, the two feet (heels) do not enter which must be closed, because it is quite difficult to carry out activities. Every book of exegesis that is a human product has its disadvantages and advantages. Each complements each other, and enriches.